Empirical Validation of Static Electricity Animation Videos to Improve the Cognitive Abilities of Physics Science in Junior High School Students - Hasibuan, Cynthia; Zulirfan, Z; Syafi’i, Muhammad (Journal of Indonesian Science Teachers, 2023)
This research aimed to determine the perceptions of students and teachers and describe the cognitive abilities of students after learning using static electricity animation videos. The research sample consisted of 31 students of class IX-6 who were randomly selected. The researcher gave a questionnaire sheet that had been validated by experts as a research instrument in collecting teacher and student responses regarding the practicality of the media with 10 indicators of practicality and gave 20 post-test questions which were analyzed descriptively. The results showed that based on teacher responses obtained an average of 3.7, student responses obtained an average level of media practicality of 3.5 with a very high category and the results showed that students' cognitive abilities obtained an average of 82.2 with a good category. The results of teacher and student responses as well as practicality test results concluded that animated video-based learning media on static electricity material was effective and practical to use as learning media for Class IX Junior High School students.